SISTEM JARINGAN INTERNET DATA UNTUK PENDISTRIBUSIAN VLAN - PUTUASDUKI, EKA PUTRA MAHARDIKA (Universitas Dirgantara Marsekal Suryadarma, 2015)
With the internet a person is able to communicate, transmit and process the data without knowing the limits and time. If the existing technology is a lot of circulation data and will possibly involve many agencies or companies or even be established cooperation of various companies in the data traffic activity. This is where the role of a company's internet service provider or ISP (Internet sevice provider) is required, with the presence of the internet service provider company will help companies to improve the performance of the company due to savings in time and costs with the reliability and accuracy of the data information that was obtained.